The Wheat Abscisic Acid-Responsive Protein Kinase mRNA, PKABA1, Is Up-Regulated by Dehydration, Cold Temperature, and Osmotic Stress. - Holappa, L. D. (1995)
The effects of dehydration, cold-temperature treatment, and osmotic and salt stress on the expression of an abscisic acid-responsive protein kinase mRNA (PKABA1) were determined in wheat (Triticum aestivum L.) seedlings. The PKABA1 transcript was detectable at basal levels in tissues of nonstressed plants and accumulated to higher levels in shoot, scutellar, and root tissues of stressed plants. PKABA1 transcript accumulated rapidly within 2 h following dehydration and within 24 h following other treatments (cold, osmotic stress, and high salt). The accumulation of PKABA1 mRNA could not be separated temporally from that of a wheat group 3 late embryogenesis abundant mRNA during dehydration and cold treatment. High PKABA1 mRNA levels were observed in field-grown plants growing under cold winter conditions but not under warmer summer conditions. A recent GenBank data base search indicated that other plant protein kinases with similar acidic amino acid stretches as in PKABA1 have been identified, and some of these kinases are responsive to environmental signals. These results suggest that PKABA1 may be part of general environmental stress responses in wheat.